We Kept Our Towns Going : The Gossard Girls of Michigan's Upper Peninsula - Wong, Phyllis Michael (Book collections on Project MUSE., 2021)
"Phyllis Michael Wong tells the stories of the "Gossard Girls," women who sewed corsets and bras at factories in Ispheming and Gwinn in Michigan's Upper Peninsula, from the early twentieth century to the 1970s. Particularly as the Upper Peninsula's mines were exhausted and its stands of timber depleted, the Gossard Girls' income sustained both their families and the local economy"--